2017
DOI: 10.1016/j.ultsonch.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Sonophotocatalytic inactivation of E. coli using ZnO nanofluids and its mechanism

Abstract: The present study evaluated inactivation efficiency of a sonophotocatalytic process using ZnO nanofluids including ultrasonic parameters such as power density, frequency and time. The result showed that inactivation efficiency was increased by 20% when ultrasonic irradiation was combined with photocatalytic process in the presence of natural light. Comparison of inactivation efficiency in photocatalytic, ultrasonic and sonocatalytic processes using Escherichia coli as a model bacteria identified that inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…This condition leads to light generation via sonoluminescence and excitation of the catalyst surface . The excited species generate highly reactive radicals . Sonocatalysis and sonoexcitation processes have found uses in different applications, such as sonodynamic therapy, environmental pollution treatment, disinfection, and so on.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition leads to light generation via sonoluminescence and excitation of the catalyst surface . The excited species generate highly reactive radicals . Sonocatalysis and sonoexcitation processes have found uses in different applications, such as sonodynamic therapy, environmental pollution treatment, disinfection, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The excited species generate highly reactive radicals . Sonocatalysis and sonoexcitation processes have found uses in different applications, such as sonodynamic therapy, environmental pollution treatment, disinfection, and so on. Inorganic catalysts such as TiO 2, ZnO, MgO, PbSe, CdSe–graphene, and so on, have been used as catalytic sites for sonocatalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important configurations of sonochemical reactors are given below-1.Ultrasonic horn and bath 2.Dual frequency flow cell 3.Triple frequency fuel cell 4.Ultrasonic bath with longitudinal vibrations Ultrasound can be generated by various gas and liquid driven transducers, electromechanical transducers like magnetostrictive and piezoelectric. Ultrasonic bath, probe and the ultrasonic flow cell are commonly used sonication equipment (L. Zhang et al, 2017). Gogate and Kabaddi (2009) describes details of hydrodynamic cavitation, according to them hydrodynamic cavitation generated by the high RPM of any object in liquid medium.…”
Section: Types Of Cavitation and Cavitational Reactors;mentioning
confidence: 99%
“…It can be concluded that the US pretreatment enhanced the disinfection efficiency, and resulting in a low E.coli concentration in the effluent, therefore, the photoreactivation reduced. Secondly, it is hypothesized that the radicals OH generated during sonication create some sub-lethal damage effect on the cell walls and enzymes, changing the permeability of cell walls or blocking the enzymes' synthesis [29,30]. However, the exactly effect of US in the photoreactivation process is required for further verification.…”
Section: Fig5 Survival Ratio Versus Exposure Time To Photoreactivatmentioning
confidence: 99%